Novel Insights Into Refugia at the Southern Margin of the Distribution Range of the Endangered Species Ulmus laevis - Torre, Sara; Sebastiani, Federico; Burbui, Guia; Pecori, Francesco; Pepori, Alessia L.; Passeri, Iacopo; Ghelardini, Luisa; Selvaggi, Alberto; Santini, Alberto (Frontiers in Plant Science, 2022)
Riparian ecosystems, in long-time developed regions, are among the most heavily impacted by human activities, therefore the distribution of tree riparian species such as Ulmus laevis are highly affected. This phenomenon is particularly relevant at the margins of the natural habitat of the species, where populations are small and rare. In these cases, it is difficult to distinguish between relics or introductions, but it is relevant for the restoration of natural habitats and conservation strategies. The aim of our work was to study the phylogeography of the southern distribution of the species. We sequenced the entire chloroplast genomes of 54 individuals from five populations sampled across different European regions to highlight polymorphisms and analyze their distribution. Thirty-two haplotypes were identified. All the sampled populations showed private haplotypes that can be considered an indicator of long-term residency, given the low mutation rate of organellar DNA. The network of all haplotypes showed a star-like topology and Serbian haplotypes were present in all branches. The Balkan population showed the highest level of nucleotide and genetic diversity. Low genetic differentiation between populations was observed but we found significant differentiation among Serbia vs other provenances. Our estimates of divergent time of U. laevis samples highlight the early split of above all Serbian individuals from other populations, emphasizing the reservoir role of Serbian population white elm genetic diversity.